Rotary Automated Portable Parking System - Suryawanshi Swapnil; Bhorde Abhishek; Agawane Harshal; Kate Pratik; Prof. Sachin Tandale (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Lack of space availability has always been a problem in urban areas and major cities and to add to it there are cars parked callously on the streets that further limit the space. In order to handle the issue of parking in busy places various types of vehicle parking systems are used worldwide namely Multi- level Automated Car Parking, Automated Car Parking System, Volkswagen Car Parking and many more. The present project work is aimed to develop a reduced working model of a car parking system for parking 6 to 24 cars within a parking area of 32.17 m². It is an amalgamation of the already developed parking systems with the added advantage of reduced space occupancy by the design of a simpler and compact parking system that is rotary and occupies vertical parking space. The chain and sprocket mechanism is used for driving the parking platform and a one fourth hp brake motor shall be implemented for powering the system and indexing the platform. The platform is fabricated to suit the working model. The procurement and manufactured items are in hand and are ready to be assembled with the structure. This model is further useful for various branches of engineering in order to develop different types of automations like PLC, micro controller and computerization. By testing and analyzing the working model we can definitely get the view to develop the parking lots at difficult and busy commercial places.
Keywords: Design Automation; Load Modeling; Mechanical Parking System; Rotary Parking System